ASEAN ECONOMIC DYNAMICS: ECONOMIC SOCIETY, OPPORTUNITY, AND CHALLENGE IN DISRUPTION ERA IN INDONESIA 2015-2020 - Ma'arif, Hilman Mahmud Akmal; Rahmawati, Baiq Ulva; Kamil, Muh (Jurnal Politica, 2023)
This study discusses Indonesia's interests in the AEC as a Regionalism Effort for Development of Domestic Capital by major ASEAN countries. In the formation of the AEC, Indonesia has a strategic position to carry out its regional political role for the domestic and regional. This is natural if this happens, because Indonesia has a vast territory and has abundant resources. The global economy keeps the wheels of the economy spinning and forces it to continue to experience changes in its transactional style. The ASEAN Economic Community (AEC) is a manifestation of the realization of a free market in the Southeast Asian region which was born from the association of cross-regional countries and development regionalism, or the regional complex formed by the domestic capital interests of several major ASEAN countries. This article is examined by using one of the concepts of internationalrelations, namely regionalism. With a qualitative research methodology approach that comes from scientific journals, scientific papers and news sources as a source of reference. The findings of this study indicate that the existence of the MEA is able to make it a medium for domestic economic development and fusion of multiculturalism within a single cluster of the Southeast Asian region.AbstrakPenelitian ini membahas tentang kepentingan Indonesia dalam MEA sebagai Upaya Regionalisme Pengembangan Modal Dalam Negeri oleh negara-negara besar ASEAN. Dalam pembentukan MEA, Indonesia memiliki posisi yang strategis untuk menjalankan peran politik regionalnya baik domestik maupun regional. Wajar jika hal ini terjadi,karena Indonesia memiliki wilayah yang luas dan memiliki sumber daya yang melimpah. Perekonomian global membuat roda perekonomian terus berputar dan memaksanya untuk terus mengalami perubahan gaya transaksionalnya. Masyarakat Ekonomi ASEAN (MEA)merupakan wujud terwujudnya pasar bebas di kawasan Asia Tenggara yang lahir dari perhimpunan negara-negara lintas kawasan dan pembangunan regionalisme, atau kompleks kawasan yang dibentuk oleh kepentingan modal domestik beberapa negara besar. negaranegara ASEAN. Artikel ini ditelaah dengan menggunakan salah satu konsep hubungan internasional yaitu regionalisme. Dengan pendekatan metodologi penelitian kualitatif yang bersumber dari jurnal ilmiah, karya ilmiah dan sumber berita sebagai sumber referensi.Temuan penelitian ini menunjukkan bahwa keberadaan MEA mampu menjadikannya sebagai media pembangunan ekonomi domestik dan perpaduan multikulturalisme dalam satu klaster tunggal kawasan Asia Tenggara.